TRILHAS INTERPRETATIVAS COMO INSTRUMENTOS DE GEOTURISMO E GEOCONSERVAÇÃO: Caso da trilha do Salto São Jorge, Campos Gerais do Paraná - Folmann, Ana Cláudia; Pinto, Maria Ligia Cassol; Guimarães, Gilson Burigo (Geo UERJ, 2010)
doi: 10.12957/geouerj.2010.1487